2022
DOI: 10.1007/s11154-022-09755-4
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, testosterone and cortisol balance, and ageing men

Abstract: Sleep serves important biological functions, and influences health and longevity through endocrine and metabolic related systems. Sleep debt, circadian misalignment and sleep disruption from obstructive sleep apnea is widespread in modern society and accumulates with life because recovery sleep is not completely restorative. Accumulated disordered sleep throughout life impacts the ageing process and the development of age-related diseases. When epidemiological and interventional studies are considered collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 135 publications
0
15
0
Order By: Relevance
“…Moreover, disturbances in sleep homeostasis are often accompanied by increased activity of the hypothalamic-pituitary-adrenal (HPA) axis, leading to elevated circulating levels of stress hormones (e.g., cortisol in humans, corticosterone in rodents). Elevated corticosteroid levels lead to decreased testosterone production ( Gao et al, 2002 ; Nollet et al, 2020 ; Liu and Reddy, 2022 ). These findings are consistent with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, disturbances in sleep homeostasis are often accompanied by increased activity of the hypothalamic-pituitary-adrenal (HPA) axis, leading to elevated circulating levels of stress hormones (e.g., cortisol in humans, corticosterone in rodents). Elevated corticosteroid levels lead to decreased testosterone production ( Gao et al, 2002 ; Nollet et al, 2020 ; Liu and Reddy, 2022 ). These findings are consistent with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, direct comparisons between these studies are challenging due to differing study populations and doses. The relationship between sex hormones and sleep is likely complex, involving interactions with other hormones such as cortisol and inflammatory markers (Liu and Reddy, 2022). Longitudinal studies are necessary to further explore this complex relationship, specifically monitoring effects of AAS during withdrawal and use.…”
Section: Sleep Quality Poorer During Aas Withdrawalmentioning
confidence: 99%
“…Underlying mechanisms proposed to associate SDB with the cardiometabolic conditions include: chronic hypoxemia, particularly nightly exposures to intermittent hypoxemia and re-oxygenation 10 ; dysregulated proinflammatory responses 11 ; increased oxidative stress 12 , imbalanced gut microbiome 13 , hormonal imbalance 14 , among others. Emerging evidence has shown that intermittent hypoxemia, especially high frequency desaturations, modulates the inflammatory response differently from chronic sustained hypoxemia 15 .…”
Section: Introductionmentioning
confidence: 99%